Differential Isotope Labeling of Glycopeptides for Accurate Determination of Differences in Site-Specific Glycosylation - Pabst, Martin; Benešová, Iva; Fagerer, Stephan R; Jacobsen, Mathias; Eyer, Klaus; Schmidt, Gregor; Steinhoff, Robert; Krismer, Jasmin; Wahl, Fabian; Preisler, Jan; Zenobi, Renato (Journal of proteome research, 2016)
We introduce a stable isotope labeling approach for glycopeptides that allows a specific glycosylation site in a protein to be quantitatively evaluated using mass spectrometry. Succinic anhydride is used to specifically label primary amino groups of the peptide portion of the glycopeptides. The heavy form (D4(13)C4) provides an 8 Da mass increment over the light natural form (H4(12)C4), allowing simultaneous analysis and direct comparison of two glycopeptide profiles in a single MS scan. We have optimized a protocol for an in-solution trypsin digestion, a one-pot labeling procedure, and a post-labeling solid-phase extraction to obtain purified and labeled glycopeptides. We provide the first demonstration of this approach by comparing IgG1 Fc glycopeptides from polyclonal IgG samples with respect to their galactosylation and sialylation patterns using MALDI MS and LC-ESI-MS.
Keywords: posttranslační úpravy proteinů; Glycopeptides; hmotnostní spektrometrie s elektrosprejovou ionizací; glykosylace; Glycosylation; Humans; lidé; Spectrometry, Mass, Electrospray Ionization; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Succinic Anhydrides; Immunoglobulin G; anhydridy kyseliny jantarové; proteomika; glykopeptidy; imunoglobulin G; izotopové značení; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Isotope Labeling; Proteomics; Protein Processing, Post-Translational